PENGARUH PENDIDIKAN KEWIRAUSAHAAN, KEPERCAYAAN DIRI DAN KREATIVITAS TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNTAG SURABAYA - Via Agustin, Citra Eka; Pratiwi, Ni Made Ida; Mulyati, Awin (Research Journal of Social Science and Economics, 2025)
The problem that is currently difficult to overcome and becomes an obstacle to the development of a country is unemployment. Unemployment occurs because the number of people in the labor force is not proportional to the available jobs. In addition, the impact of Covid-19 also has an impact and pressure on almost all sectors of life. Realizing this importance, current students must try to become graduates who don't only want to work as office employees. Students must also be able to create jobs such as opening a business. But not all students have an interest in entrepreneurship. One of the things needed in running a business is having knowledge about entrepreneurship education, having high self-confidence and creativity. Given the importance of interest in entrepreneurship in college students, the authors conducted a study entitled The Influence of Entrepreneurship Education, Self-Confidence and Creativity on Interest in Entrepreneurship in Students of the Faculty of Economics and Business Untag Surabaya. This study aims to analyze the effect of Entrepreneurship Education, Self-Confidence and Creativity on Students of the Faculty of Economics and Business Untag Surabaya. As for supporting this research, the author in making his thesis uses a type of quantitative research using multiple linear regression methods. Partially it appears that there is no significant effect on Entrepreneurship Education and Self Confidence in Students of the Faculty of Economics and Business Untag Surabaya. While partially there is a significant influence on Creativity in Students of the Faculty of Economics and Business Untag Surabaya.